Overview of the Genus Pseudocercospora on Vitaceous Plants in Korea with Introduction of Pseudocercospora neovitis sp. nov. - Ardhianita Indi Nur Aida; Lamiya Abasova; Hye-Ryeong Jang; Ji-Woon Jeong; In-Young Choi; Hyeon-Dong Shin (Mycobiology, 2025)
Several Pseudocercospora species were recognized as leaf spot pathogens on various vitaceous plants worldwide. Of them, Pseudocercospora vitis on Vitis spp. and Ps. ampelopsidis on Ampelopsis glandulosa var. heterophylla were reported to occur in Korea to date. The species diversity of the genus Pseudocercospora associated with vitaceous plants in Korea was revised in the scope of multigene sequence analyses and detailed morphological examinations. This study includes the introduction of new host finding for Ps. vitis, Vitis labrusca × Vitis vinifera “Campbell Early” in Korea, and one new species, Ps. neovitis sp. nov. on Vitis flexuosa. Illustrations of diseased plants with micrographs of pathogens, generated phylogenetic trees, and a discussion, including comparisons with related Pseudocercospora species are presented here.